การเตรียมและการใช้ประโยชน์เลคตินตอนจูเกตจากเลคตินของเมล็ดจำปาดะ - ประภาพร อุทารพันธุ์ (มหาวิทยาลัยสงขลานครินทร์, 2024)
Lectins are carbohydrate-binding proteins. They show specific binding to carbohydrates thus sugar specificity is basic characteristics of lectins. Lectins have more than one binding sites which allow them to agglutinate cells and/or precipitate glycoconjugates. The binding of lectins to carbohydrates is loose and reversible. In this study, purification of lectin from the Champaada (Artocapus integer) seed extract was achieved by chromatography on Sephadex G-200 column followed by N-acetyl galactosamine-agarose column. The purified lectin was found to exist in 2 forms of proteins, one major and one minor bands with M, of 14,000 and 16,800, respectively. It had a molecular weight of 46,000 Daltons, as determined by gel filtration. The purified lectin contained highly specific hemagglutinating activity for rabbit red blood cells. It also agglutinated rat immature sperm better than mature sperm. Conjugation of the purified lectin to peroxidase was performed by periodate- oxidation and chromatography on Sephadex G-200 column. The lectin-peroxidase conjugate (LPC) had a molecular weight of 90,150 Daltons, as determined by gel filtration. LPC could stained rat epididymal sperm. It was found to distribute over the whole surface of the mature sperm whereas it was localized mainly in the head region of the immature sperm. The membrane fractions were extracted from 2 types of the sperm and subsequently analyzed by SDS-PAGE following by Westem blot. There are 5 protein bands (M, 38,000, 53,000, 81,000, 95,000 and 120,000) from the membrane fraction of the mature sperm and 4 protein bands (M, 32,000, 52,000, 85,000 and 100,000) from the membrane fraction of the immature sperm which were stained by LPC.By using quantitatively binding analysis, the amount of LPC bound to rat sperm found to be 1.03 x 10 and 0.58 x 10 μg/cell for the mature and the immature sperm, respectively. To study carbohydrate specificity of lectin, enzyme-linked lectin binding assay (ELLBA) was developed. ELLBA was performed by direct coating of microtiter plate with streptavidin (SAV). Biotin-galactose conjugate (BG) was synthesized and used to bind to the immobilized SAV. The bound conjugate was then detected using LPC. The maximal inhibition and the concentration for half maximal inhibition values were compared among 6 sugars tested; 5 were inhibitory in the following decreasing order methyl-a-D-galactoside, N-acetyl galactosamine, galactose, N-acetyl glucosamine and methyl-B-D-galactosamine. Fucose was non-inhibitory. The purified lectin and Helix pomatia agglutinin showed moderate inhibition whereas mucin and bovine serum albumin showed no inhibitory effect. Its sensitivity is much higher than that of hemagglutination inhibition test.